Enhancing Gut Health: Probiotic Interventions in Preterm Neonates with Necrotizing Enterocolitis - Rahmah Yasinta Rangkuti; Muhammad Nazhif Haykal; Erna Furaidah (Journal of Medicine and Health Technology, 2026)
Necrotizing enterocolitis (NEC) remains a significant challenge in neonatal care, particularly in preterm neonates, due to its high mortality and morbidity rates. Probiotics, defined as live microorganisms that confer health benefits to the host, have emerged as a promising intervention to enhance gut health and reduce the risk of NEC. This study aimed to evaluate the role and efficacy of probiotic interventions in preterm neonates with NEC by analysing existing literature and clinical studies. Data on the types of probiotics used, their mechanisms of action, dosage regimens, and clinical outcomes were extracted and analysed. The findings revealed that specific strains of probiotics, including Lactobacillus and Bifidobacterium, significantly reduced the incidence of NEC and associated mortality in preterm neonates. Probiotics were found to modulate gut microbiota, enhance mucosal integrity, and reduce systemic inflammation, thereby mitigating the pathogenesis of NEC. The study also highlighted variations in the efficacy of different probiotic strains and dosing strategies, indicating a need for standardized protocols. The results underscore the potential of probiotics as a preventive and therapeutic tool for NEC in preterm neonates. Future research should focus on identifying optimal probiotic strains, dosages, and long-term safety profiles to establish robust clinical guidelines and improve neonatal outcomes.